Determining client cognitive status following mild traumatic brain injury - Hobson, E.; Lannin, N.; Taylor, A.; Farquhar, M.; Morarty, J.; Unsworth, Carolyn (Informa Healthcare, 2016)
Background: People with mild traumatic brain injury (mTBI) commonly experience cognitive impairments. Occupational therapists working in acute general hospitals in Australia routinely access client Glasgow Coma Scale (GCS) scores, and assess cognitive status using standardized tools and by observing basic activity of daily living (ADL) performance. However, limited evidence exists to identify the best assessment(s) to determine client cognitive status. Aim/objectives: To determine whether cognitive status assessed by GCS score and the Cognistat are predictive of basic ADL performance among clients with mTBI in an acute general hospital and make inferences concerning the clinical utility of these assessment tools. Material and methods: Retrospective analysis of medical record data on demographics, Cognistat, GCS, and modified Barthel Index (MBI) using descriptive statistics, chi-square tests and linear regression. Results: Data analysis of 166 participants demonstrated that no associations exist between GCS and Cognistat scores, or Cognistat scores and MBI dependency level. The presence of co-morbid multi-trauma injuries and length of stay were the only variables that significantly predicted MBI dependency level. Conclusion and significance: While the MBI scores are of value in identifying clients with difficulty in basic ADLs, Cognistat and GCS scores are of limited use in differentiating client levels of cognitive impairment and the authors caution against the routine administration of the Cognistat following mTBI. Further research is required to identify more suitable assessments for use with a mTBI population.